Absence behavior as traffic crash predictor in bus drivers - af Wåhlberg, Anders E.; Dorn, Lisa (Elsevier, 2009)
Problem: Various indicators of health have been shown to be associated with traffic crash involvement. As general health is also related to absence from work, the latter variable may be more strongly related to crashes, especially for professional drivers. Method: Bus driver absence from work was analyzed in association with their crash records. Two British samples and one Swedish sample were used. Results: One of the British samples yielded fair correlation between crash record and absence, while for the other the effect was restricted to the first three months of driving. The Swedish data had effects in the expected direction but these were not significant. Discussion: The use of an indirect, overall measurement of health, may be a viable method for predicting the traffic crash involvement for professional drivers, although replications are needed in larger samples and other populations. Impact on industry: The use of absence records for the identification of at risk drivers would seem to be a simple and useful method for companies with major fleets, and it also shows the importance of promoting employee health and well being at work as a potential method of reducing the cost, not only of absenteeism, but also of crashes in company vehicles.
Keywords: Traffic crash Accident Bus driver Absence Exposure motor-vehicle accidents obstructive sleep-apnea automobile accidents absenteeism involvement frequency risk